PENERAPAN METODE DAN TEKNOLOGI PRE-CAST KOLOM DAN BALOK TRICON 3 JUPITER PADA KONSTRUKSI BANGUNAN GEDUNG BERTINGKAT - Yuslan Irianie (INFO-TEKNIK, 2013)
Infrastructure building rusunawa plays a major role in promoting the development of an area and arrangement of residential areas in a city. The construction technology columns and pre-cast concrete beams is an alternative form of construction structures are evolving at this time the world of construction of high-storey building and others in Indonesia. Tricon system 3 jupiter erection erection begins with a column mounted on the module point that has been determined and for the next column column reinforcement entered on all minimal 40D and bracing is installed at the top end of the column and then do grouting column spacing filled in grouting with grouting equipment. Erection beam made after the column, where the beams rested dikolom approximately 3-5 cm then entered the ring joint totaling 4-6 ring linked to overlap dibendrat cuttings, the next step installation bakesting then carried out joint grouting beam-column joint. For the construction slab rested on beams Tricon 3 jupiter. Methods of execution of work Rusunawa that begins with preparatory work, then proceed with the job of building structures under and job fabrication / production of pre-cast, further work on the ground floor (install components of columns, beams and slabs and then grouting and cast stairs), after it resumed work floor 2 (repeated stages on the ground floor) then the account after grouting while experiencing the drying process is done architectural work on the 1st floor after it was done more work on the 3rd floor of the structure, so sterusnya on the floor next to the work of roof coverings and final finishing work.